HUBUNGAN KOORDINASI MATATANGAN DENGAN KETEPATAN SMASH DALAM PERMAINAN BOLA VOLI DI KLUB BKD TEMBILAHAN KABUPATEN INDRAGIRI HILIR - devit wilastra (Jurnal Olahraga Indragiri, 2017)
This study is purposed to determine the extent of the relationship of hand eye coordination with the accuracy of smash in the game volleyball club BKD Tembilan Indragiri Hilir. Type of research was correlational. Population in this research is athletes daughter club BKD Tembilahan regency indragiri downstream population amounted to 14 people.The sample was taken by using Kriejce table with significancy level of 0.05 so that there were 12 people. Data were collected through tests, observations, and documentation.Instruments that researchers use is a hand eye coordination test and test accuracy smash bolavoli. In the data analysis used Product Moment Test analysis. From the results of data analysis show that r count 0.802> r table 0.576 and t count 4.247> t table 2.228 then Ho rejected and Ha in received.Researchers found that there is a significant relationship between hand eye coordination with smash accuracy in a volleyball game at the club BKD Tembilahan Indragiri Hilir district, with a relationship of 64% with a value of r 0.620 in very strong category.